Oral Facial Manifestations of Sanjad-Sakati Syndrome: A Literature Review - Sara Alghamdi (MDPI AG, 2022)
Aim: To perform a comprehensive review of orofacial manifestations of Sanjad-Sakati syndrome (SSS). Methods: A comprehensive electronic literature search was performed using PubMed, Scopus and Cochrane library databases. The search keywords included were "Sanjad-Sakati syndrome (SSS)", "dental manifestations", "dental management", "oral health", "dental care for patients with SSS", "dental health of people with SSS", "caries", and "oral hygiene". The inclusion criteria were papers published only in English, papers published by August 2021, and papers discussing orofacial manifestations of SSS and language. Results: The search of the databases retrieved eleven case reports and three case series studies. Overall, 56 cases (11 case reports and 3 case series studies) were reported on Sanjad-Sakati syndrome in the published literature. The majority of the reports are from the Middle Eastern region. Conclusions: The reported orofacial manifestations of SSS include beaked nose, depressed nasal bridge, enamel hypoplasia, hypodontia, low-set ears, posteriorly rotated ears, deep-set eyes, microcephaly, microdontia, micrognathia, prominent forehead, retrognathia, and thin lips. The review paper also establishes the importance of the dental under general anesthesia in SSS individuals.